PENGARUH LITERASI DIGITAL KEUANGAN DAN EFIKASI KEUANGAN TERHADAP PERILAKU INVESTASI (Studi Kasus Pada Mahasiswa Magister Manajemen Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin) - Akbar Barito Putra; Rahmi Widyanti; Husnurropiq Husnurropiq (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2022)
The purpose of this study is to 1. To find out and analyze financial digital literacy partiallyinfluence the investment behavior of students of Master of Management Study Program class 2020. 2.To find out and analyze financial efficacy partially influence investment behavior of Master ofManagement Study Program students of class 2020. 3 To find out and analyze the influence offinancial digital literacy and financial efficacy simultaneously on the investment behavior of studentsof the 2020 Master of Management Study Program.Research design is qualitative research. The population in this study were 78 respondents.Sampling using the slovin 0.05 formula resulted in a total of 65 respondents. With purposive samplingtechnique. The data collection technique used a questionnaire as many as 35 question items with ascale of 1 to 5 and tested with validity and reliability data. Technical analysis of data to answer thehypothesis using the SPSS 26.0 application. With the technique of multiple linear regression analysis.The results of the study can be concluded that digital financial literacy has a partial effect oninvestment behavior with a t-count value of 2.136 > a t-table value of 1.999 with a significance valueof 0.036 (sig <0.05) and financial efficacy partially affects investment behavior by the t-count value is6.337 > the t-table value is 1.999 with a significance value of 0.000 (sig <0.05) and has a significanteffect on investment behavior of students of the 2020 Master of Management study program with asignificant level of 0.000 (sig <0.05). Thus it can be interpreted that the independent variables includefinancial digital literacy and financial efficacy simultaneously and significantly affect the dependentvariable, namely student investment behavior.